Awareness of aerosol-related transmission of COVID-19 among the dentists of Nepal - Nashib Pandey; Buddha Bahadur Basnet; Sushmit Koju; Anju Khapung; Alka Gupta (Nature Publishing Group, 2021)
Abstract Objective To access the awareness of dental practitioners of Nepal towards COVID-19 transmission through aerosols. Materials and methods The study involved 384 dentists from all over Nepal and was conducted for a period of 3 months. A self-reported online questionnaire was developed using Google forms and the link was shared. It emphasized the awareness related to the aerosol and ventilation system in their daily practices was prepared. The data were analyzed in Statistical Package for Social Sciences version 20.0 software. Results The majority of participants were female 52.9% (n = 203) and within the age groups of <30 years 57% (n = 219). Participants from Bagmati Province were 60.4% (n = 232), with least from Sudurpaschim Province 0.5% (n = 2). 60% of participants provided only emergency services during the COVID-19 pandemic and few (7%) provided consultations via telephone. The current ventilation system used was a well-ventilated room with open windows 65.4% (n = 251). However, 52.8% (n = 203) preferred specialized operatory incorporating high-efficiency particulate air (HEPA) filters and ultraviolet (UV) light. More than 60% of respondents were unaware of the particle size of the aerosol. Conclusions The obtained results signify the need for the proper ventilation system with appropriate air filtration systems in dental clinical setups.